Evaluation of a surgical training programme for clinical officers in Malawi. Issue 2 (8th January 2019) - Gajewski, J; Borgstein, E; Bijlmakers, L; Mwapasa, G; Aljohani, Z; Pittalis, C; McCauley, T; Brugha, R
Abstract: Background: Shortages of specialist surgeons in African countries mean that the needs of rural populations go unmet. Task-shifting from surgical specialists to other cadres of clinicians occurs in some countries, but without widespread acceptance. Clinical Officer Surgical Training in Africa (COST-Africa) developed and implemented BSc surgical training for clinical officers in Malawi. Methods: Trainees participated in the COST-Africa BSc training programme between 2013 and 2016. This prospective study done in 16 hospitals compared crude numbers of selected numbers of major surgical procedures between intervention and control sites before and after the intervention. Volume and outcomes of surgery were compared within intervention hospitals between the COST-Africa trainees and other surgically active cadres. Results: Seventeen trainees participated in the COST-Africa BSc training. The volume of surgical procedures undertaken at intervention hospitals almost doubled between 2013 and 2015 (+74 per cent), and there was a slight reduction in the number of procedures done in the control hospitals (–4 per cent) ( P = 0·059). In the intervention hospitals, general surgery procedures were more often undertaken by COST-Africa trainees (61·2 per cent) than other clinical officers (31·3 per cent) and medical doctors (7·4 per cent). There was no significant difference in postoperative wound infection rates for hernia procedures at intervention hospitals between trainees and medical doctors ( P = 0·065). Conclusion: The COST-Africa study demonstrated that in-service training of practising clinical officers can improve the surgical productivity of district-level hospitals. Graphical Abstract: This implementation research project developed, implemented and evaluated Malawi's first postgraduate surgical training programme for non-physician clinicians. The training model has proved to be effective and has been embedded within the mainstream educational programmes offered in the country. Implementing training standards